The Influence of Human Resource Management on Job Satisfaction: A Study on Five Star Hotel Employees in Jakarta - Ramha, Anunggita (Generasi Sains Indonesia, 2024)
This study investigates the impact of Human Resource Management (HRM) practices on job satisfaction among employees in five-star hotels in Jakarta. Utilizing a quantitative research design, the study collected data from 200 employees through a structured questionnaire that assessed various HRM practices, including training and development, employee engagement, work-life balance, and recruitment. The results reveal significant positive relationships between these HRM practices and job satisfaction, with training and development (B = 0.40, p < 0.001) and employee engagement (B = 0.50, p < 0.001) emerging as the strongest predictors. The findings highlight the importance of adopting comprehensive HRM strategies that not only enhance employee satisfaction but also contribute to improved organizational performance and customer service quality. This research provides valuable insights for hotel management seeking to create a motivated and satisfied workforce in a competitive industry.